Istiglâlu Barâati al-Ikhtirâ’ fî al-Qânûn al-Indûnîsî Dirâsah Fiqhiyah Taqwîmiyah - Husnul Haq; Arif Ali Arif (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2020)
Patent has a prominent place in people’s nowadays lives as it becomes the main mover of their advancement as well as a barometer of a nation’s development and treasure. Countries with a huge percentage of patents occupy higher position and get stronger political influence than others. Therefore, the worldwide countries have agreed to conduct agreements to protect the patent through so called Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS). Indonesian’s signing on the agreement was then followed by a legal cover in the field of patent through Law number 13 of 2016. This study aims to examine the concept of exploitation in the Indonesian Law using Islamic jurisprudence as the evaluative instrument. It focuses on how far the congruity between both in portraying the patent and punishment for its exploitation is. We use analytical and critical method as well as comparative ones. The careful study on this law and Islamic jurisprudence including its principles and purposes makes it clear that both agree on patent as a part of wealth and property and therefore, it needs protection as well as rules on punishment for the aggressors. Both also share the same opinion on patent exploitation rules whether personal exploitation or through a license contract. However, Islamic jurisprudence has established procedures for patent exploitation and one of which is that it should not harm others.